PENGARUH EFEKTIFITAS MODUL AJAR BERBASIS STEAM TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - sulispiana (Cocos Bio, 2025)
Abstract: This study aims to: (1) Develop a STEAM-based biology teaching module to improve students' critical thinking skills. (2) Determine the feasibility and practicality of the STEAM-based biology teaching module. (3) Determine the effectiveness of the STEAM-based teaching module. This development research uses the Borg and Gall model, which is carried out with 7 development stages, namely: initial information collection, planning, initial product development, small-scale trials, product revision, limited-scale trials, and product revision. The trial subjects in this study were material experts, design experts, biology teachers, 20 students from the small-scale trial, and 70 students from the limited-scale trial at SMAN 1 Pringgasela. The data collection technique was carried out using a questionnaire and the data were analyzed using quantitative descriptive analysis techniques. Based on the results of data analysis and discussion, it can be concluded that the STEAM-based biology teaching module product to improve students' critical thinking skills is feasible, practical, and effective for use during the learning process. This feasibility can be seen from the average feasibility percentage obtained from material experts 87.03%, design experts 97.08%, and biology teachers 90.97% so it is included in the very feasible category. Furthermore, the practicality of the teaching module can be seen from the average practicality score from student responses, which is 2.82 and is included in the practical category. Then the effectiveness of the teaching module can be seen from the average N-Gain obtained from the limited scale test of the experimental class 0.79 and the limited scale test of the control class 0.46. Based on the average N-Gain obtained, it has moderate criteria with a fairly effective level of effectiveness. Based on the results of the average percentage of STEAM-Based Student Worksheets per group, it shows that the STEAM-Based Student Worksheets to improve students' critical thinking skills are in the critical category.  Keywords: Teaching Module, Student Worksheet, Borg and Gall, Science, Technology, Engineering, Art, and Mathematics (STEAM), Critical Thinking.